First record of the genus Eugalta Cameron, 1899 (Hymenoptera: Ichneumonidae: Poemeninae) from Vietnam - Nhi, Pham Thi; Long, Khuat Dang; Achterberg, Cornelis van (Academia Journal of Biology, 2018)
The genus EugaltaCameron, 1899 (Ichneumonidae: Poemeniinae) is reported for the first time from Vietnam after studying the Ichneumonidae collections recently assembled at the Institute of Ecology and Biological Resources (Ha Noi) and the Naturalis Biodiversity Center(Leiden). A key to seven species of Eugaltais compiled. Eugaltapunctulatayamuna(Gupta, 1980), is a junior synonym of the nominate subspecies, E. punctulatapunctulata Cameron, 1899, syn. nov. Citation: Pham Thi Nhi, Khuat Dang Long, Cornelis van Achterberg, 2017. First records of the genus Eugalta Cameron, 1899 (Hymenoptera: Ichneumonidae: Poemeniinae) from Vietnam. Tap chi Sinh hoc, 39(4): 467-473. DOI: 10.15625/0866-7160/v39n4.11242. *Corresponding author: ptnhi2@yahoo.com Received 5 December 2016, accepted 12 August 2017